STUDI DESKRIPTIF TINGKAT PENGETAHUAN IBU MENYUSUI TENTANG ASI EKSKLUSIF DI PUSKESMAS CILACAP UTARA - Astuti, Lelia Kusuma (Universitas Ahmad Dahlan, 2009)
Background: Breastfeeding in Indonesia has not fully implemented. Efforts to increase breastfeeding behavior in women who have exclusively breastfed infants in particular is still considered insufficient. The main problem is the socio-cultural factors, awareness of the importance of breastfeeding, health services and health workers who have not fully support the PP-ASI, vigorous promotion of formula milk and the mother worked. Knowledge mother became one of the factors that influence exclusive breastfeeding. Phenomenon that occurs in the region of Central Cilacap district, was found in mothers who have not given exclusively breastfed their babies and mothers still do not know the benefits of exclusive breastfeeding.Method: This was rurvey research using descriptive method. Data collection was spread out questionnaires, then the data obtained are processed statistically by descriptive analysis and presented in tabular form the frequency distribution. The number of respondents as many as 80 people.Result: The results showed that respondents who had a level of knowledge of both exclusive breastfeeding as much as 78%, the level of knowledge was 19%, and who have less knowledge level of 3%. White exclusive breasfeeding in the health center of Central Cilacap 60% and 40% of respondents did not give their babies breast milk exclusively.Conclusion: Women who have knowledge of both exclusive breastfeeding is not always given exclusively breasfed their babies, because there are many other factors that influence exclucive breasfeeding. Keywords : The knowledge of exclusive breastfeeding, exclusive breastfeeding